2015
DOI: 10.1097/cmr.0000000000000180
|View full text |Cite
|
Sign up to set email alerts
|

Adapted ECHO-7 virus Rigvir immunotherapy (oncolytic virotherapy) prolongs survival in melanoma patients after surgical excision of the tumour in a retrospective study

Abstract: An oncolytic, nonpathogenic ECHO-7 virus adapted for melanoma that has not been genetically modified (Rigvir) is approved and registered for virotherapy, an active and specific immunotherapy, in Latvia since 2004. The present retrospective study was carried out to determine the effectiveness of Rigvir in substage IB, IIA, IIB and IIC melanoma patients on time to progression and overall survival. White patients (N=79) who had undergone surgical excision of the primary melanoma tumour were included in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 26 publications
0
88
0
5
Order By: Relevance
“…Numerous pre-clinical and clinical successes have been reported [1,2], and currently three OVs are approved for clinical use: herpes simplex virus 1 (HSV-1)-based T-VEC for melanoma, approved in the USA and later in the European Union [3]; enteric cytopathic human orphan virus 7-based RIGVIR for melanoma, approved in Latvia, Georgia and Armenia [4]; and adenovirus type 5-based Gendicine and Oncorine for head and neck squamous cell carcinoma in China [5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous pre-clinical and clinical successes have been reported [1,2], and currently three OVs are approved for clinical use: herpes simplex virus 1 (HSV-1)-based T-VEC for melanoma, approved in the USA and later in the European Union [3]; enteric cytopathic human orphan virus 7-based RIGVIR for melanoma, approved in Latvia, Georgia and Armenia [4]; and adenovirus type 5-based Gendicine and Oncorine for head and neck squamous cell carcinoma in China [5].…”
Section: Introductionmentioning
confidence: 99%
“…Rigvir targets CD55/DAF-3, a GPI-anchored protein present on cancer cells, and has the ability to elicit both humoral and T-cell-mediated anti-tumor responses. (66, 67) A retrospective study of Rigvir in patients with stage IB-IIC melanoma found that Rigvir significantly prolonged survival and reduced mortality, without record of any “untoward” side effects(68), and a case report showed prolonged survival in patients with stage IV M1c melanoma treated with Rigvir. (69) The case report data has limited applicability, as it was obtained retrospectively and lacked a control arm.…”
Section: Oncolytic Viruses Used In the Treatment Of Melanomamentioning
confidence: 99%
“…Онколитические вирусы уже применяются в клинической практике. В 2004 г. в Латвии был одобрен препарат Rigvir, созданный на основе природного штамма эховируса 7-го типа [3,18]. Была показана его способность пода-влять различные виды рака, такие как меланома, рак желудка, рак прямой и толстой кишки, рак поджелудочной железы, рак почки, рак мочево-го пузыря, рак шейки матки, а также различные виды саркомы [3].…”
Section: аутологичные т-лимфоциты и клетки несущие химерные антигеннunclassified